Transgender people and sports - Ewelina Kamasz (Kazimierz Wielki University, 2018)
The essence of sport and fair play is predicated on the assumption that individuals must fall in with one of the preordained categories of female or male. To compete as an athlete, individuals must align themselves as female or male and join the corresponding team. This is not a difficult task for a cisgender person but a transgender one is inevitably going to face unique challenges posed by this binary or dualistic view of sex. This paper considers the precarious situation of transgender athletes and their extraordinary body self-narratives. I review sport policies and the enforcement of the woman's and man's category in sport. I present the barriers and facilitators of physical activity and sport participation among young, transitioning adults. Finally, I would like to muse over the ethis of inclusion of transgender and intersex athletes into a mainstream sport and I discuss whether and on which conditions should transwomen be permitted in female categories in sports.